What is the prevalence of untreated depression and death ideation in older people? Data from the Irish Longitudinal Study on Aging. - Kennelly, Sean; Kenny, Rose; Tobin, Katy; Briggs, Robert (My University, 2018)
Objective: Late life depression (LLD) confers significant morbidity and mortality but is well recognized that it often goes undetected or untreated. The objective of this study is to quantify the burden of untreated depression and death ideation (DI) at a population level. Design: Cross-sectional study ascertaining the prevalence of, and factors associated with, untreated depression and DI. Setting: This study, embedded within the Irish Longitudinal Study on Ageing, involves over 7,000 community-dwelling people aged ≥50 years. Measurements: Depression was defined as Centre for Epidemiological Studies Depression scale ≥16 indicating current clinically relevant depressive symptoms or Composite International Diagnostic Interview indicative of major depressive episode within the last year. Participants not prescribed antidepressants/antipsychotics were defined as untreated. To define DI, participants were asked “In the last month, have you felt like you would rather be dead?” Results: In total, 12% (839/7,055) met criteria for depression with 29% (241/839) on pharmacological therapy. Those with untreated depression were less likely to endorse symptoms of persistent low mood or worthlessness, but there was no difference in age or general practitioner (GP) visits compared to those on treatment. Over 3% (223/7,055) of participants had DI and less than one-third had visited their GP within the last year. Conclusions: This study demonstrates that two-thirds of depressed older people are not prescribed antidepressant/antipsychotic therapy. It is important to raise awareness of depression among older people and healthcare professionals, with particular focus on the fact that LLD is not an inevitable consequence of ageing and effective treatment is available.
PUBLISHED
Keywords: late life depression, mood, death ideation, undiagnosed, untreated; Ageing